Risk factors affecting perioperative analgesic efficacy in transurethral resection of the prostate and the impact of mind map—guided nursing on pain management: a retrospective study - Wu, Huifeng; Wen, Biyun; Liu, Jiaqian; Yu, Yanfang (Frontiers in Surgery, 2025)
PurposeThis study aimed to analyze the factors influencing perioperative analgesic efficacy in Transurethral Resection of the Prostate (TURP) and evaluate the effectiveness of mind map-guided nursing interventions in reducing perioperative pain and improving nursing quality.MethodsA retrospective analysis was conducted on clinical data from 140 patients who underwent TURP surgery at our institution between January and December 2023. Following PRISMA guidelines, patients were systematically screened and stratified into two groups based on analgesic efficacy 72h post-surgery: good analgesic response group (Visual Analogue Scale [VAS] score ≤6) and poor analgesic response group (VAS score >6). Univariate analysis was performed on clinical parameters, followed by multivariate logistic regression analysis on statistically significant factors to identify independent risk factors affecting perioperative analgesic efficacy. To address potential multicollinearity between ASA classification and comorbidities, variance inflation factor (VIF) analysis was conducted. Subsequently, 80 patients with poor analgesic response were randomized into two equal groups (n = 40 each): an observation group receiving mind map-guided nursing intervention and a control group receiving standard nursing care. Outcome measures included VAS scores, psychological status (anxiety and depression), sleep quality, urinary incontinence severity, and nursing satisfaction. The certainty of evidence was assessed using the GRADE approach.ResultsOf the 152 eligible patients screened, 140 met inclusion criteria and were analyzed. Univariate analysis revealed that the poor analgesic response group had significantly longer operation times and higher proportions of American Society of Anesthesiologists (ASA) class II patients, smokers, and individuals with hypertension or diabetes (all P < 0.05). Multivariate logistic regression identified prolonged operation time (OR = 1.528, 95% CI: 1.218–1.982) and smoking history (OR = 1.278, 95% CI: 1.042–1.826) as independent risk factors for poor perioperative analgesic response. ROC curve analysis demonstrated good predictive accuracy (AUC = 0.782, 95% CI: 0.705–0.859). The mind map-guided intervention group demonstrated significantly lower post-intervention scores for pain (VAS), anxiety, depression, sleep disturbance, and urinary incontinence compared to the control group (all P < 0.05). Additionally, nursing satisfaction rates were significantly higher in the intervention group (95.00% vs. 75.00%, P < 0.05).ConclusionPerioperative analgesic efficacy in TURP patients is significantly influenced by operation duration and smoking history as independent risk factors. Mind map-guided nursing intervention effectively reduces postoperative pain, improves psychological outcomes, and enhances patient satisfaction, warranting its broader clinical implementation.